TEACHING HISTORY FOR TRUTH AND RECONCILIATION: THE CHALLENGES AND OPPORTUNITIES OF NARRATIVITY, TEMPORALITY, AND IDENTITY - Miles, James (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2018)
This paper argues that history educators and teachers are uniquely implicated in the Truth and Reconciliation Commission’s Calls to Action through their responsibility to teach Indigenous and Canadian history, including the injustices of settler colonialism. After examining the politics of Canada’s ongoing truth and reconciliation process, this paper articulates three conceptual challenges for history education in pursuit of reconciliation: narrativity, temporality, and identity. This paper concludes by suggesting possible pedagogical opportunities for each of these challenges, taking into consideration a historical thinking approach to teaching and learning now embedded in most provincial and territorial curricula.